Application of liquid crystal thermography for temperature measurement of the absorber plate of solar air heater. (2022) - Kumar, Dheeraj; Choudhury, Ramit; Layek, Apurba
Abstract: Thermochromic liquid crystals (TLC) have indeed been utilized effectively in quasi heat transport and fluid dynamic research in recent years. Researchers in the areas of heat transfer and flow circulation have long used TLCs to map surface and spatial temperature changes. Before TLCs can be utilized for quantitative temperature measurements, they must first be calibrated to determine their color–temperature relationship. The goal of this article is to provide new and intermediate TLC users with an overview of the fundamentals and difficulties of TLC calibrations, with a focus on surface thermography. The first part of the article provides a comprehensive overview of thermochromic liquid crystals and the liquid crystal thermography technique. The final part of this paper concludes with a description of how liquid crystal thermography, both steady and transient, may be used to study heat transfer in turbulent flows. In the present article, Surface temperature TTLC is evaluated with the color response of TLC sheets and thermodynamic properties can be further calculated with the thermal relationship provided. The Imaging, colorimetry, lighting, and expected measurement error are all important elements of TLC calibration are discussed in this article.